The Effect Of Using Flashcard To Improve Students’ Present Continous Tense At Second Grade Of Islamic Junior High School Mu’allimin Muhammadiyah Bangkinang - Dicky Al Fajri; Citra Ayu; putri asi Lestari (FKIP - Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the effect of using flashcards to improve students' understanding of the Present Continuous Tense at Islamic Junior High School Mu’allimin Muhammadiyah Bangkinang. The research uses an experimental design with two groups: the experimental group, taught using flashcards, and the control group, taught with traditional teaching methods. Data were collected through pre-test and post-test assessments administered to both groups. The results showed that while the experimental group showed an improvement in post-test scores, the difference between the experimental and control groups was not statistically significant, with a p-value > 0.05. However, the effect size analysis showed that the use of flashcards had a small effect on students' understanding. The study concludes that while flashcards can enhance students' understanding, their impact is not large enough to be considered significant. The study also suggests that flashcards should be used as part of a more interactive and varied teaching approach.